2013
DOI: 10.1093/aje/kws588
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Among Tetrafluoroethylene Synthesis and Polymerization Workers

Abstract: Tetrafluoroethylene (TFE), a compound used for the production of fluorinated polymers including polytetrafluoroethylene, increases the incidence of liver and kidney cancers and leukemia in rats and mice. This is the first time the cancer risk in humans has been explored comprehensively in a cohort mortality study (1950-2008) that included all polytetrafluoroethylene production sites in Europe and North America at the time it was initiated. A job-exposure matrix (1950-2002) was developed for TFE and ammonium pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 20 publications
0
56
0
Order By: Relevance
“…A job-exposure matrix with annual semiquantitative estimates for TFE and PFOA were considered sufficient to identify relative differences in exposure to both compounds. Consonni et al 14 reported an SMR of 1.4 (95% CI 0.7 to 2.7) for kidney cancer in the cohort, but could not separate the effects of TFE and PFOA with kidney cancer in their exposure trend analyses. It is possible the results of Steenland and Woskie12 are similarly confounded by TFE.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A job-exposure matrix with annual semiquantitative estimates for TFE and PFOA were considered sufficient to identify relative differences in exposure to both compounds. Consonni et al 14 reported an SMR of 1.4 (95% CI 0.7 to 2.7) for kidney cancer in the cohort, but could not separate the effects of TFE and PFOA with kidney cancer in their exposure trend analyses. It is possible the results of Steenland and Woskie12 are similarly confounded by TFE.…”
Section: Discussionmentioning
confidence: 91%
“…Although PFOA and TFE exposures were highly correlated, Steenland and Woskie12 considered only PFOA in their analysis indicating that they assumed that TFE's volatile and explosive properties meant it would be well controlled under normal operations, and thus render appreciable exposure to it unlikely. By contrast, another evaluation of TFE synthesis and polymerisation workers (including 40% from the DuPont plant),14 23 reported potential TFE exposure occurring through leaks, opening autoclaves in the polymerisation area, or from decomposition of the polymer. A job-exposure matrix with annual semiquantitative estimates for TFE and PFOA were considered sufficient to identify relative differences in exposure to both compounds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All but two studies were conducted in the United States (17,21), and all but one were cross-sectional, retrospective cohort, or ecological studies (25). In six studies, PFAS exposure was associated with increased mortality from kidney-related cancers (18)(19)(20)(21)(22)24); however, the strength of the association varied, with standardized mortality ratios ranging from 1.07 to 12.8 ( Figure 3).…”
Section: Human Epidemiologic Studiesmentioning
confidence: 99%
“…We believe that such results are of interest since they are based on a substantial number of cases (a total of 16 cases of stomach cancer and 8 cases of kidney cancer), and regard organs included by IARC as targets for various substances to which the cohort had been exposed: cadmium, arsenic, lead arsenates, trichloroethylene. A study on the long‐term effects of exposure in a cohort of 4,773 workers assigned to the production and/or use of tetrafluoroethylene (TFE) has recently been published; this also includes workers at the Fraschetta plant [Consonni et al, ]. The results of the mortality study highlighted increased risks—not statistically significant—for liver and kidney cancers, as well as leukemia; all such outcomes have been suggested by experimental studies [National Toxicology Program, ].…”
Section: Discussionmentioning
confidence: 99%